Buruh Gendong dan Kesejahteraan: Strategi Yasanti Melawan Patriarki di Kalangan Pekerja Informal di Yogyakarta - Felisitas Friska Dianing Puspa (Jurnal PolGov, 2023)
This paper analyzes the efforts of Yasanti, a civil society organization in Yogyakarta, in increasing empowerment in order to reduce the patriarchal culture of the Pasar Beringharjo Carrying Women Workers group in the context of a pandemic. This article answers the question of how the pandemic hit the economy of women carrying workers, where there was a decline in wages due to market closures. Also the lack of protection obtained by informal workers. This study is important to see the reality of informal workers during the pandemic, especially women carrying women in Pasar Beringharjo , which is the center of Yogyakarta's tourism economy. Carrying workers are a group of informal workers who do not have social protection such as standard wage insurance, health insurance and old age insurance. This presents economic problems that affect the welfare of women carrying women. These carrying workers also play a dual role, namely carrying out economic roles and holding responsibility for domestic affairs. The carrying workers' association, which was initiated by Yasanti, has become a solidarity for carrying workers in maintaining the welfare that the government does not get. The study of Yasanti's strategy was carried out using qualitative methods with case studies to be able to provide answers to the formulation of the problem. Thus, the study of this topic is able to open a further discussion regarding work protection for the welfare of informal workers. The issue of the manifestation of the wage gap obtained by the Pasar Beringharjo Labor group in Yogyakarta during the pandemic.